Reproducibility of Fixed-luminance and Multi-luminance Flicker Electroretinography in Patients With Diabetic Retinopathy Using an Office-based Testing Paradigm. (November 2020) - Wroblewski, John J.; McChancy, Christa; Pickel, Kassandra; Buterbaugh, Hunter; Wieland, Tyler; Gonzalez, Alberto
Background: We evaluated the reproducibility of office-based flicker electroretinography (ERG) in patients with nonproliferative diabetic retinopathy (NPDR). Methods: An observational study was conducted in which ultra-widefield fluorescein angiography (UWF-FA) was performed on 20 patients with mild-to-moderate NPDR; images were graded by the Fundus Photography Reading Center (Department of Ophthalmology and Visual Sciences, University of Wisconsin, Madison, WI, USA). Fixed- and multi-luminance flicker ERG was repeated four times (greater than or equal to seven days apart). Recording consistency was assessed using intra-class correlation coefficients (ICCs), coefficients of variation, and Pearson correlations. Results: 82.5% and 17.5% of eyes had mild and moderate NPDR using UWF-FA; 90% of the angiograms were given a high confidence grade. Fixed-luminance phase values were highly reproducible (ICC: 0.949; P < .001). There was a significant negative correlation between fixed-luminance phase and log-corrected ischemic index values (−0.426; P = .015). Conclusions: Office-based, fixed-luminance phase values are highly reproducible and negatively correlate with retinal ischemia in NPDR, suggesting that global retinal dysfunction may be reliably quantified early in patients with diabetes.